Alpha‐Lipoic Acid Modulates the Oxidative and Inflammatory Responses Induced by Traditional and Novel Tobacco Products in Human Liver Epithelial Cells. Issue 3 (9th February 2023) - Reis, Rengin; Kolci, Kübra; Bahcivan, İrem; Coskun, Goknil Pelin; Sipahi, Hande
Abstract: Smoking has been associated with NAFLD recently, thus might be a contributing factor for liver disease progression. In this study, we identified the modulative action of α‐lipoic acid (α‐LA), an organosulphur compound, towards heated tobacco product (HTP) and cigarette smoke extract (CSE)‐induced oxidative stress and inflammation in human liver HepG2 cells. The cells were pre‐treated with α‐LA and exposed to tobacco extracts, and cytotoxicity, oxidative response (SOD, CAT activities and GSH, MDA levels), inflammation (nitrite, IL‐6, AhR levels), and liver function (AST/ALT) were assessed. According to the results, a notable increase in oxidative response was observed with CSE, whereas GSH depletion and decreased SOD activity were the key toxicological events induced by HTP (p<0.05). The oxidative and inflammatory responses were ameliorated with α‐LA treatment, particularly through GSH restoration and IL‐6 modulation. To conclude, these findings on α‐LA might contribute to the design of novel adjuvant therapies for people exposed to tobacco smoke. Abstract :